Pengaruh Orientasi Kewirausahaan Dan Strategi Bisnis Terhadap Kinerja Usaha (Studi Kasus Pada Usaha Pembenihan Ikan Nila Di Desa Bumi Harjo Batanghari Lampung Timur) - Damia Latifa; Febriyanto; Selamet Fuadi (Jurnal Manajemen DIVERSIFIKASI, 2025)
This research is motivated by the problem of the high level of competitiveness of tilapia hatchery businesses that sell similar seeds, the lack of business capital to develop businesses such as adding ponds and reaching customers outside the city, the lack of optimal managerial ability in managing the business, the low level of skill of tilapia hatchery business actors in utilizing technology and workforce capabilities that are not yet professional because they have not gone through clear selection only emphasize brotherhood. This research aims to find out whether entrepreneurial orientation and business strategy individually and together have an effect on business performance. The sample for this research was tilapia hatchery business actors in Bumi Harjo Village, Batanghari, East Lampung, totaling 50 respondents. The research method uses a quantitative type of research. Data collection used questionnaires, and data analysis used validity tests, reliability tests, normality tests, linearity tests, homogeneity tests, multiple linear regression analysis, t tests, f tests, coefficient of determination r2 tests and statistical hypotheses using SPSS version 25 program tools. The results of this research show that (1) entrepreneurial orientation has a positive and significant effect on business performance with a tcount of 25.944 > ttable 2.011 and sig 0.000 > 0.05. (2) business strategy has a positive and significant effect on business performance with a tcount of 32.717 > ttable 2.011 and sig 0.000 > 0.05. (3) entrepreneurial orientation has a positive and significant effect on business performance with a value of fcount > ftable 3.20 and sig 0.000 > 0.05.